Monetary and credit policies in the Bahamas since 1974 - Francis, Carlene Y. (Institute of Social and Economic Research KingstonJM, 1986)
Discusses the objectives of monetary and credit policy. Outlines the tools of monetary and credit control that the Central Bank is empowered to use, viz. loans and advances. Reviews monetary and credit developments and policies over the period 1976-1986. Discusses the limitations of monetary policy in the Bahamian context.